2011
DOI: 10.1007/s00418-011-0880-5
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate-based colocalization analysis of single-molecule localization microscopy data

Abstract: Colocalization of differently labeled biomolecules is a valuable tool in fluorescence microscopy and can provide information on biomolecular interactions. With the advent of super-resolution microscopy, colocalization analysis is getting closer to molecular resolution, bridging the gap to other technologies such as fluorescence resonance energy transfer. Among these novel microscopic techniques, single-molecule localization-based super-resolution methods offer the advantage of providing single-molecule coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
206
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(214 citation statements)
references
References 25 publications
(37 reference statements)
3
206
0
Order By: Relevance
“…2A) and developed an analysis strategy that combines cluster detection and colocalization analysis. The degree-of-colocalization (DoC) analysis (29) determines the local density for each molecule at increasing radii, providing a density gradient for each channel (Fig. 2B).…”
Section: Cd3ζ Molecules Exist In Nanoclusters That Increase In Molecularmentioning
confidence: 99%
See 2 more Smart Citations
“…2A) and developed an analysis strategy that combines cluster detection and colocalization analysis. The degree-of-colocalization (DoC) analysis (29) determines the local density for each molecule at increasing radii, providing a density gradient for each channel (Fig. 2B).…”
Section: Cd3ζ Molecules Exist In Nanoclusters That Increase In Molecularmentioning
confidence: 99%
“…Two-Color Colocalization Analysis. The two-color data were analyzed using a modified version of the coordinate-based colocalization method (29). The first step in the analysis is to remove molecules which are isolated, by excluding points with a local density below a random distribution (total density = total number of molecules/total area of region of interest).…”
Section: Primary Mouse Ot-i Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence images produced by stochastic optical reconstruction microscopy (STORM) allows superior subcellular localization of proteins and visualization of interacting proteins as adjacent particles at nanometer resolution (21). Direct STORM (dSTORM) (22) relies on the reversible photoswitching of fluorophores.…”
Section: K Atp Channel Subunits Associate With Plakoglobin Andmentioning
confidence: 99%
“…It turns out that the most commonly used parameter, the so-called Pearson's Correlation Coefficient (PCC) is superior to the Manders Overlap Coefficient [13,14] (MOC) which is currently implemented in most commercial software packages for image processing [15]. A closer look at the PCC, however, reveals that it has some frequently cited major drawbacks which significantly limit its utility for colocalization analysis in certain cases [16][17][18][19][20]. For example, it was found that the PCC, which can adopt values between þ1 and À1 as a measure of the similarity of channels (+1: perfect colocalization; values between 0 and À1: no colocalization), is very sensitive to strong intensity fluctuations or threshold variations.…”
Section: Biophotonicsmentioning
confidence: 99%